Monitoring System For Decorative Plants Using Arduino Nano Microcontroller - Rizky Fitria Haya; Chicha Rizka Gunawan; Fazri Amir (Ultima Computing : Jurnal Sistem Komputer, 2020)
Ornamental plants are used to decorate the room or the yard. In the current technology era where everyone has a high level of activity, it sometimes makes them forgot to pay attention to the ornamental plants in their homes. Therefore, the purpose of establishing this plants monitoring system is to determine the condition of the plant by displaying smile and sad face images on the LCD. This system uses a microcontroller likes Arduino Nano as the main controller and connected to other sensors such as the LDR sensor, soil moisture, and DHT11. The results of this study indicate that the ornamental plant is in good condition if it displays happy face, that is when the results of the lighting, soil moisture, and temperature are obtained accordance the values set in the program. Otherwise, if the system displays a sad face, it shows that the condition of the ornamental plants is not good because of the lack of lighting, soil moisture, and low temperatures received by the ornamental plants. The values set on the soil moisture and lighting sensor are in the range of 50% to 95%, while the values set on the temperature sensor are in the range of 15°C to 35°C.